Enhanced Steganography using K-MATRIX - Arora, Komal Singh; Gandhi, Geetanjali (International Journal of Computer Sciences and Engineering, 2014)
Information hiding for security in data transmission is in the air as long as the conversion of data before sending it. Steganography is the art and the science of hiding information or data by embedding within other. Steganography works by replacing bits of useless or unused data in various files (graphics, sound, text or even floppy disks) through LSB technique and this hidden data can be plain text, cipher text or images. But this technique usually takes more time if encryption is done first for improving its security. The aim of this paper is to hide the data after encrypting it through new approach called K-Matrix, which will provide less time complexity than the existing technique for cryptography.